Pemberdayaan UMKM Melalui Pelatihan Penyusunan Laporan Keuangan Berbasis Aplikasi MYOB di Desa Padurenan, Kabupaten Kudus - Anita Rahmawaty; Siti Zulfa Nadiya (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
The main issue of this activity is embroidery and convection products as one of the main commodities of Kudus. Both superior products are developed in Padurenan village which has great potential for productive economic development, but its financial performance is still very limited. The purpose of this activity is to provide training on preparing financial reports to MSME actors to improve their financial performance. The method of this activity is in the form of training in preparing financial reports based on the MYOB application using 3 methods, namely the lecture, practice, and discussion methods. The material in this training is MSME accounting and the practice of preparing financial reports using the MYOB application. The results of the community service training showed that there was an increase in the financial performance of the MSME embroidery and convection cluster in Padurenan Village, Kudus. After the training activities, MSMEs are increasingly skilled at compiling financial reports using the MYOB application so that they can improve their financial performance.